Clinical profile and prognostic indicators of Plasmodium Falciparum Malaria in children(1-12 years) - Poorva Gohiya; Manjusha Goel; Rashmi Dwevedi; S Renwal (International Journal of Medical Research and Review, 2014)
Introduction: Malaria is one of the oldest recorded diseases of world, it has infected humans since last 50,000 years .Pediatric population is especially vulnerable to this preventable illness. This study has been undertakento ascertain the incidence of common clinical features of falciparum malaria so that to improve the insight into this highly prevalent disease and to evaluate prognostic indicators of falciparum malaria.Materials and Methods: The study has been conducted in Department of Pediatrics ,Gandhi Medical College Bhopal (MP),over a period of one year.150 cases of slide positive falciparum malaria were studied thoroughly using a preformed proforma. Clinical features, biochemistry, course during stay, response to treatment and outcome were recorded in all the study patients.Results: Majority of our cases were males of more than five years. Fever was presenting symptom in 98% of patients. Vomiting, altered sensorium, convulsions, breathlessness, headache, bleeding were the other symptoms recorded in that order. Pallor was the most common clinical sign (96%) followed by hepatomehaly & splenomegaly(57 & 65%), hypotension(30%), dehydration(25%) and icterus(28%). Serum creatinine value of >3 gm/dl (10%)and Hemoglobin level of <5gm/dl was significantly associated with mortality(p value <0.05).Incidence of severe falciparum malaria was 36% in our study out of which 29% expired.Conclusions: Severe anaemia and cerebral malaria are the most common presenting features in the pediatric population as per our study. Serum creatinine levels of > 3 gm/dl and haemoglobin levels of <5gm/dl were significantly associated with mortality. The signs significantly associated with mortality were; Glasgow Coma Scale <8, splenomegaly, neck rigidity.